New Virgulid Cercaria (Trematoda, Lecithodendroidea) from Freshwater Mollusk Melanopsis praemorsa (Melanopsidae) from Azerbaijan Water Bodies. Morphology and Chaetotaxy of Cercaria agstaphensis 31 - Manafov, A.A. (Вестник зоологии, 2012)
An illustrated morphological description with chaetotaxy and differential diagnosis of a new virgulid cercaria – Cercaria agstaphensis 31 from the freshwater prosobranchial mollusk Melanopsis praemorsa (Linnaeus, 1758) are given. Special attention is paid to the arming of the tegument, structure of the glandular apparatus, excretory system, digestive system, structure of the sensory apparatus and other larval morphological characters. Приводятся рисунки, описание морфологии, в том числе и хетотаксии, а также дифференциальный диагноз новой виргулидной церкарии — Cercaria agstaphensis 31 из пресноводного переднежаберного моллюска Melanopsis praemorsa (Linnaeus, 1758). Особое внимание уделено вооружению тегумента, строению железистого аппарата, экскреторной системы, пищеварительной системы, строению сенсорного аппарата и других индивидуальных особенностей организации стилетных виргулидных церкарий.